Evaluation of Lupus Cases Related to TNF Inhibitors in Children - Şeyma Türkmen; Nelgin Gerenli; Betül Sözeri (Galenos Publishing House, 2023)
Systemic lupus erythematosus (SLE) due to anti-tumor necrosis factor (TNF) agents is a rare entity. We reported three cases who developed lupus-like syndrome while receiving infliximab therapy for various reasons. All cases demonstrated clinical and laboratory findings of SLE. And all of them needed treatment. We would like to emphasize that the risk of anti-TNF-alpha-induced lupus should be kept in mind in patients receiving anti-TNF therapy for any reason.